Clinical applications, accuracy and limitations of guided endodontics: a systematic review. (23rd October 2019) - Moreno‐Rabié, C.; Torres, A.; Lambrechts, P.; Jacobs, R.
Abstract: Background: The novel concept of guided endodontics has been reported as an effective method to obtain safe and reliable results in root canal treatment. Aim: To evaluate by means of a systematic review the clinical applications, accuracy and limitations of guided endodontic treatment. Data sources: A search of the literature was performed on PubMed, Embase, Web of Science and Cochrane Library databases, until 25 April 2019. No language or year restrictions were applied. Study eligibility criteria: Articles that answered the research question, including case reports, in vitro and ex vivo studies were included. Data extraction was performed independently by two reviewers. Study appraisal: Quality assessment was done using STROBE, CARE and Modified CONSORT guidelines for observational, case reports and pre‐clinical studies, respectively. Results: A total of 22 articles, including fifteen case reports, six pre‐clinical studies ( in vitro and ex vivo studies) and one observational study, were included. Limitations and Conclusions: Even though the level of evidence is low, and the methodology described among studies heterogeneous, all articles describe guided access cavity preparation and guided surgery as being highly accurate and successful techniques when comparing the drilled path to the planned treatment. More studies with a larger number of patients are necessary to obtain significant conclusions.